Efektivitas Layanan Konseling Kelompok dengan Teknik Self-Management untuk Menurunkan Perilaku Membolos pada Siswa Kelas XI IPS SMA Negeri 2 Kupang - Rizaldy, Afrizal Rifky; Upa, Muhammad Dae Pua; Korohama, Katharina E. P. (Prodi Bimbingan Konseling FKIP UNDANA, 2023)
This study aims to investigate the effectiveness of group counseling with self-management techniques to decrease truancy behavior in class XI IPS students at SMA Negeri 2 Kupang. This study used a quantitative approach with a pre-experimental research type with a one-group pre-test and post-test research design. This research was conducted at SMA Negeri 2 Kupang. The sampling technique used was the purposive sampling method, that is, the sample was taken according to the intent and purpose of the study where the pre-test would be given to all members of the population, totaling 132 students. The data collection technique uses a questionnaire with a Likert scale model. The data analysis technique used is descriptive analysis, paired sample t-test differential analysis with SPSS For Windows 21 Version program. The results of this study indicate that there is a decrease in students' truancy behavior after being given group counseling services using self-management techniques. This is evidenced by the difference in the mean score before being given treatment of 119.60 and the mean score after being given treatment of 75.70. In addition, the t count using the paired sample t-test is 46.886, this value is > t-table 1.833 with a sig value <0.05, which means that H0 is rejected. This finding shows that group counseling services with self-management techniques potentially that used to reduce truancy behavior in class XI IPS students at SMA Negeri 2 Kupang.